Purification, biochemical, and immunological characterisation of a major food allergen: different immunoglobulin E recognition of the apo- and calcium-bound forms of carp parvalbumin. Issue 5 (1st May 2000) - Bugajska-Schretter, A; Grote, M; Vangelista, L; Valent, P; Sperr, W R; Rumpold, H; Pastore, A; Reichelt, R; Valenta, R; Spitzauer, S
Abstract : BACKGROUND: Almost 4% of the population suffer from food allergy which is an adverse reaction to food with an underlying immunological mechanism. AIMS: To characterise one of the most frequent IgE defined food allergens, fish parvalbumin. METHODS: Tissue and subcellular distribution of carp parvalbumin was analysed by immunogold electron microscopy and cell fractionation. Parvalbumin was purified to homogeneity, analysed by mass spectrometry and circular dichroism (CD) spectroscopy, and its allergenic activity was analysed by IgE binding and basophil histamine release tests. RESULTS: The isoelectric point (pI) 4.7 form of carp parvalbumin, a three EF-hand calcium-binding protein, was purified to homogeneity. CD analysis revealed a remarkable stability and refolding capacity of calcium-bound parvalbumin. This may explain why parvalbumin, despite cooking and exposure to the gastrointestinal tract, can sensitise patients. Purified parvalbumin reacted with IgE of more than 95% of individuals allergic to fish, induced dose-dependent basophil histamine release and contained, on average, 83% of the IgE epitopes present in other fish species. Calcium depletion reduced the IgE binding capacity of parvalbumin which, according to CD analysis, may be due to conformation-dependent IgE recognition. CONCLUSIONS: Purified carp parvalbumin represents an important cross reactive food allergen. It can be used for in vitro and in vivo diagnosis of fish-induced food allergy. Our finding that the apo-form of parvalbumin had a greatly reduced IgE binding capacity indicates that this form may be a candidate for safe immunotherapy of fish-related food allergy.